Molecular Detection of Babesia spp. (Apicomplexa: Piroplasma) in Free-Ranging Canids and Mustelids From Southern Italy - Santoro, Mario; Auriemma, Clementina; Lucibelli, Maria Gabriella; Borriello, Giorgia; D'Alessio, Nicola; Sgroi, Giovanni; Veneziano, Vincenzo; Galiero, Giorgio; Fusco, Giovanna (Frontiers in Veterinary Science, 2019)
Babesiosis is an emerging tick-borne disease caused by apicomplexan parasites with widespread geographical distribution and various wildlife species as reservoir hosts. The aims of this study were to investigate the prevalence and assess the role of free-ranging canids and mustelids in the maintenance of Babesia spp. in southern Italy. PCR analysis of splenic samples targeting the 18S rRNA gene revealed the presence of Babesia spp. in 36 of 82 (43.9%) red foxes (Vulpes vulpes) including 29 (58%) from Campania region and seven (21.8%) from Calabria region, in seven of 13 (53.8%) Eurasian badger (Meles meles), and in one of 13 (7.7%) grey wolf (Canis lupus). Samples from other host species including 9 Eurasian otters (Lutra lutra), 1 stone marten, 1 least weasel (Mustela nivalis), and 1 European polecat (Mustela putorius) tested Babesia spp. negative. Sequence analysis of the 18S rRNA gene demonstrated the presence of B. vulpes in the red fox and two sequence types of badger-associated Babesia spp. in the Eurasian badger. The Babesia sp. sequence detected in the grey wolf was identical to a badger-associated Babesia sp. This study shows that the number of Babesia spp. infecting free-ranging carnivores in Italy is higher than currently believed, and suggests that these hosts may play an important role in the maintenance of the sylvatic cycle of these parasites. It is the first report of badger-associated Babesia spp. in Italy and in a grey wolf.